Community voice in cross-sector alignment: concepts and strategies from a scoping review of the health collaboration literature - Aliza Petiwala; Daniel Lanford; Glenn Landers; Karen Minyard (BMC, 2021)
Abstract Background Health care access is an important driver of population health, and factors beyond health care also drive health outcomes. Recognizing the importance of the social determinants of health (SDOH), different actors in the health care, public health, and social service sectors are increasingly collaborating to improve health outcomes in communities. To support such collaboration, the Robert Wood Johnson Foundation developed a cross-sector alignment theory of change. According to the cross-sector alignment theory of change, community voice is critical for helping collaboratives address community health needs. Yet research on health collaboratives offers mixed guidance on how community voice should be understood and which community voice strategies are most effective. Methods This study addresses a gap in the literature with a systematic scoping review of research on health-oriented cross-sector collaboration and community voice. By scanning key academic journals, searching three academic databases, and obtaining documents from across our professional networks, we identified 36 documents that address community voice in health collaboratives. Results The review reveals several conceptions of community voice and a range of community voice strategies. We find that community voice strategies fall on a spectrum between two broad types of approaches: active and passive. These vary not only in the level of power shared between communities and collaborators, but also in the level of involvement required from the community, and this in turn has important implications for community collaboration strategies. We also find that while most strategies are discussed in the context of short-term collaboration, many also lend themselves to adoption in the context of sustainable collaboration and, ultimately, cross-sector alignment. Conclusion This review provides a characterization and conceptualization of community voice in health-oriented collaborations that provides a new theoretical basis for future research. Passive and active community voice strategies can be studied in more detail for their expected impact on health outcomes and disparities. Increased attention to active community voice and the resources it requires can help practitioners achieve improved health outcomes and researchers understand the pathways to health improvement through collaboration.